2004
DOI: 10.1038/sj.sc.3101652
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular fat and glucose tolerance after spinal cord injury – a cross-sectional study

Abstract: Objective: Determine intramuscular fat (IMF) in affected skeletal muscle after complete spinal cord injury using a novel analysis method and determine the correlation of IMF to plasma glucose or plasma insulin during an oral glucose tolerance test. Setting: General community of Athens, GA, USA. Methods: A total of 12 nonexercise-trained complete spinal cord injured (SCI) persons (10 males and two females 40712 years old (mean7SD), range 26-71 years, and 875 years post SCI) and nine nonexercise-trained nondisab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
206
6
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(223 citation statements)
references
References 17 publications
(21 reference statements)
8
206
6
3
Order By: Relevance
“…With ageing, muscle strength is lost at a faster rate than lean mass, pointing to additional determinants of impaired contractility in older adults 32. Findings of appreciable increases in IMAT in the thigh of the immobilized limb are in agreement with previous observations in young5, 33 and older adults 34. Interestingly, no changes were apparent in the non‐casted limb.…”
Section: Discussionsupporting
confidence: 89%
“…With ageing, muscle strength is lost at a faster rate than lean mass, pointing to additional determinants of impaired contractility in older adults 32. Findings of appreciable increases in IMAT in the thigh of the immobilized limb are in agreement with previous observations in young5, 33 and older adults 34. Interestingly, no changes were apparent in the non‐casted limb.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, we found a marked increase in the intramuscular lipid content of all individuals with SCI compared to controls. This phenomenon of elevated muscle lipid has been reported in a number of clinical populations including individuals with stroke 15 as well as both complete 9 and incomplete SCI. 10 Elder and co-workers demonstrated that persons with complete SCI display an almost fourfold increase in intramuscular fat relative to controls, and that these values correlate with plasma glucose levels during an oral glucose tolerance test (r 2 ¼ 0.52 and 0.71, Po0.001).…”
Section: Discussionmentioning
confidence: 58%
“…Given the higher reported incidence of insulin resistance in persons with incomplete SCI 7 and a purported relatively inactive lifestyle, 8 we hypothesized that individuals with incomplete SCI would demonstrate an elevated IMCL content in skeletal muscle. Although studies have demonstrated elevated lipid depots in the lower extremity muscles of persons with complete and incomplete SCI using magnetic resonance imaging (MRI), 9,10 we are not aware of any study that has specifically investigated alterations in the IMCL content in persons with motor incomplete SCI.…”
Section: Introductionmentioning
confidence: 99%
“…16 Recent evidence suggests that thigh IMAT and subcutaneous fat areas are increased in sedentary SCI individuals and that relative IMAT is a strong predictor of plasma glucose suggesting an increased risk for impaired glucose tolerance and insulin resistance. 18 Although thigh subcutaneous fat was a strong predictor of metabolic outcomes within group, this effect was largely due to the relation to whole body fat mass and notably the relation was in the positive direction (that is, not protective). Our findings regarding thigh IMAT suggest that insulin sensitivity is associated with thigh IMAT in SCI individuals and that high-volume upper-body physical activity can protect against the risk of insulin resistance resulting from thigh IMAT accumulation and loss of muscle in this population.…”
Section: Discussionmentioning
confidence: 95%
“…Images were automatically segmented into fat, skeletal muscle and background bone regions as described previously. [16][17][18] To correct for differences in muscle area and limb size, IMAT areas of a given limb were divided by the muscle area of that limb, providing the relative IMAT for the limb. Similarly, the muscle areas and subcutaneous fat areas of a given limb were divided by the whole area of the respective limb, resulting in the relative muscle and subcutaneous fat areas for the limb.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%